2003
DOI: 10.1111/j.1572-0241.2003.07331.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Management of Hepatitis C Patients in Primary Care Clinics

Abstract: Hepatitis C testing is rarely initiated in primary care clinics based on physician-identified risk factors. Interventions should be developed to optimize early diagnosis of hepatitis C as significant liver disease may be present despite the absence of symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
47
2
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 10 publications
7
47
2
1
Order By: Relevance
“…However, only 39% of internal medicine residents and less than two-thirds of generalists mentioned that they consistently obtain this information when examining new patients [15,19,22,28]. Using a chart review of newly identified cases, investigators found very few patients were tested for HCV because of physician-identified risk factors [24].…”
Section: Screening and Testingmentioning
confidence: 98%
See 1 more Smart Citation
“…However, only 39% of internal medicine residents and less than two-thirds of generalists mentioned that they consistently obtain this information when examining new patients [15,19,22,28]. Using a chart review of newly identified cases, investigators found very few patients were tested for HCV because of physician-identified risk factors [24].…”
Section: Screening and Testingmentioning
confidence: 98%
“…The remaining three articles examined knowledge of and attitudes toward HCV infection in dentists, dental students, or nurses [10][11][12]. In 20 investigations, either the target population was randomly selected or the entire designated population was contacted for participation [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. Successful recruitment, defined as at least 75% enrollment, was reported by five of the cross-sectional studies, all but three of which relied on convenience sampling [16,17,26,30,31].…”
Section: Target Groups and Recruitmentmentioning
confidence: 99%
“…We also did not assess why more patients in opiate maintenance treatment programs did not receive HCV treatment. Clearly, there is a selection bias, although the same can be said for treatment studies in non-IDU patients [38]. In a previous screening study among Swiss patients on opiate maintenance treatment, the type and distribution of reasons for nonparticipation of hepatitis C seropositive candidates were assessed using a semistructured questionnaire [39].…”
Section: Discussionmentioning
confidence: 99%
“…A similar conclusion was made by another study which found that 46% and 62% of physicians reported that they routinely asked patients about a history of blood transfusion and injection drug use, respectively [4] . Shehab reported that HCV testing is rarely initiated in primary care clinics based on physician identified risk factors such as transfusion prior to 1992 or a history of injection drug use [1] . Similar studies among urban primary care practices, comprising patients at highest risk for exposure to HCV risk factors, have not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have suggested that hepatitis C (HBV) manage-ment is suboptimal in primary care settings [1][2][3][4][5] . In fact, only 59% of primary care physicians (PCPs) reported asking patients about HCV risk factors [3] .…”
Section: Introductionmentioning
confidence: 99%